Social origins and the role of kinship in the employment of white women workers at the Zebediela citrus estate, 1926-195? - Van Niekerk, Andrea (My University, 1986)
Social and economic developments in the larger society, economic constraints, and changes in industrial organization affect the family's ability to respond to labour markets, organize migration, and influence work processes. In turn, internal changes within the family, as well as the family's priorities, which are dictated by its needs and cultural traditions, affect labor supply, motivation for work, and social relations in the production process. According to this argument of American historian T. Hareven, it is clear that for an understanding of the adaption of white women workers on the Zebediela Estate, one has to consider the social mileau, the material and personal imperative of these workers. This essay has to remain fairly tentative though, because of the limits imposed by scant references in the company's documents, and by the small size of the survey done. Conclusions are inevitably based on the experiences of the majority of these women, i.e. those who came from the Northern Transvaal.
African Studies Seminar series. Paper presented April 28, 1986
Keywords: Citrus fruit industry. South Africa; Women. Employment. South Africa; Women, White. Employment. South Africa; Kinship. Economic aspects. South Africa